A primary adrenal adenomatoid tumor in a young woman - Krstevska, Brankica; Jovanovska Mishevska, Sasha; Ahmeti, Irfan; Jovanovska, Biljana; Bitoska, Iskra; Bogoeva, Biljana (Bioscientifica, 2014)
Adenomatoid tumors are relatively uncommon neoplasms of mesothelial origin, usually occuring in the male and female genital tracts. Rare extragenital adenomatoid tumor has been identified in adrenal gland. The differential diagnosis includes metastatic carcinoma and adrenocortical carcinoma. We present a case of 30 years old woman with incidentally radiological (ultrasound) finding of unilateral tumor in the right adrenal gland. CT and MRI were of great value in localizing this tumor. The tumor ranged from 5.6 to 6.4 sm in greatest dimension. Clinical and hormonal examinations excluded Sy. Cushing, M. Conn and pheochromocytoma. She underwent a right adrenalectomy using classic laparatomy. The large tumor (d: 8×7×3 sm) was removed and there were no extra-adrenal extension into periadrenal adipose tissue, infiltration of the adrenal cortex or medulla. Histologic examination showed numerous cystic spaces lined by flattened of cuboidal epithelial cells. The small cystic spaces are separated by oedematous fibrovascular stroma with rare epitheloid cells with vacuolated cytoplasm. Immunohistochemical steins were positive for Vimetin(+), s100(+), MCA mesothelial Ag(+), CD 68 (+) and negative for Acitin (−), CK7(−), CD3(−). Conclusions: Adenomatoid tumor is a rare neoplasm that should be added in the differential diagnosis of any adrenal tumor occurring in adrenal gland. The immunohistochemical profile of this adrenal adenomatoid tumor is very supportive of a mesothelial cell origin.